Math, asked by adwaithmanoj2006, 7 months ago

Solve 5x–2 (2x–7) = 2 ( 3x–1) + 72

Answers

Answered by assingh
0

Answer:

5x - 2( 2x - 7 ) = 2( 3x - 1 ) + 72

5x - 4x + 14 = 6x - 2 + 72

x + 14 = 6x + 70

5x = - 56

x = -56 / 5

So, answer is -56/5.

Remember :-

Negative Number * Negative Number = Positive Number

Negative Number * Positive Number = Negative Number

Positive Number * Positive Number = Positive Number

Positive Number * Negative Number = Negative Number

Thank you.

Answered by Anonymous
4

x = -56/5

Question :-

Solve 5x–2 (2x–7) = 2 ( 3x–1) + 72

solution :-

5x–2 (2x–7) = 2 ( 3x–1) + 72

➡ 5x - 4x + 14 = 6x -2 + 72

➡ x + 14 = 6x + 70

➡ x - 6x = 70 -14

➡ - 5x = 56

➡ x = 56/-5 = -56/5

Similar questions